Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the inverse of the function [tex]\(f(x) = 2x + 1\)[/tex], follow these steps:
1. Start with the given function:
[tex]\[ f(x) = 2x + 1 \][/tex]
2. Replace [tex]\(f(x)\)[/tex] with [tex]\(y\)[/tex] for easier manipulation:
[tex]\[ y = 2x + 1 \][/tex]
3. Solve for [tex]\(x\)[/tex] in terms of [tex]\(y\)[/tex]. First, isolate the term with [tex]\(x\)[/tex]:
[tex]\[ y - 1 = 2x \][/tex]
4. Next, solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{y - 1}{2} \][/tex]
5. Now replace [tex]\(y\)[/tex] with [tex]\(x\)[/tex] to write the inverse function:
[tex]\[ h(x) = \frac{x - 1}{2} \][/tex]
6. Simplify the expression:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
This matches the form given in one of the options. Therefore, the inverse function is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
Given the choices:
- [tex]\( h(x) = \frac{1}{2} x - \frac{1}{2} \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x + \frac{1}{2} \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x - 2 \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x + 2 \)[/tex]
The correct answer is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
1. Start with the given function:
[tex]\[ f(x) = 2x + 1 \][/tex]
2. Replace [tex]\(f(x)\)[/tex] with [tex]\(y\)[/tex] for easier manipulation:
[tex]\[ y = 2x + 1 \][/tex]
3. Solve for [tex]\(x\)[/tex] in terms of [tex]\(y\)[/tex]. First, isolate the term with [tex]\(x\)[/tex]:
[tex]\[ y - 1 = 2x \][/tex]
4. Next, solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{y - 1}{2} \][/tex]
5. Now replace [tex]\(y\)[/tex] with [tex]\(x\)[/tex] to write the inverse function:
[tex]\[ h(x) = \frac{x - 1}{2} \][/tex]
6. Simplify the expression:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
This matches the form given in one of the options. Therefore, the inverse function is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
Given the choices:
- [tex]\( h(x) = \frac{1}{2} x - \frac{1}{2} \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x + \frac{1}{2} \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x - 2 \)[/tex]
- [tex]\( h(x) = \frac{1}{2} x + 2 \)[/tex]
The correct answer is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.